Examining the impact of business incubation on the growth of tourism SMMEs: the case of Pilanesberg business Incubator Programme (PBIP) - Simango, Soza Sydney (Graduate School of Business (GSB), 2023)
The Small Micro and Medium Enterprises (SMMEs) sector plays an important role in driving economic growth and development in both large and emerging economies. Direct benefits of SMME development include job creation, innovation and the enhancing of social justice. The tourism industry in South Africa is largely comprised of small-scale firms with low barriers to entry, and is a major contributor to entrepreneurial development, innovation, economic growth and job creation. There is, however, a 70% failure rate of SMMEs in South Africa despite available public and private enterprise support programmes within the small business ecosystem. In many sectors globally, business incubation is widely regarded as an economic development tool which is commonly used to assist fledgling small business to grow and eventually compete in the market independently. Based on the state-funded Pilanesberg Business Incubation Programme (PBIP), the study used both qualitative and quantitative methods to investigate the impact business incubation makes on the growth and development of tourism SMMEs. The 3-year business incubator enrolled 50 small-scale tourism enterprises comprising of operators of accommodation and hospitality, travel and tour operators/agencies, events and attractions, and arts and crafts businesses. The results align to a significant extent with existing studies which have found business incubation to contribute to the growth of emerging enterprises. Incubates of the Pilanesberg Business Incubation Programme were found to realise an upsurge in market exposure. The market exposure in turn resulted in increased demand, marginal rise in revenue, both retained and created new jobs, and stimulated expansion in existing and new products/ service offerings during and post the three years of incubation